Report on the Observance of Standards and Codes, Accounting and Auditing : Module B - Institutional Framework for Corporate Financial Reporting, B.8 Accounting Standard-setting - World Bank (World Bank, Washington, DC, 2017)
The purpose of this report is to gain an understanding of the governance arrangements and procedures for setting accounting and financial reporting standards in a jurisdiction, covering: (a) the adoption of International Financial Reporting Standards (IFRS) where applicable, and (b) national generally accepted accounting principles (GAAP). The questions are based on examples of good practice followed by internationally-recognized standard-setting bodies. The report is structured as follows: institutional environment for standard-setting; adoption of IFRS; standard -setting process for national auditing standards; and other aspects of the standard-setting process.